Anticariogenic properties of Solanum ferox L. ethanol extract - Siti Zaleha, Raduan; Abdul Aziz, M.W.H. (Faculty of Dentistry, University of Malaya, 2018)
Solanum ferox L. is a plant species which belongs to the Sola-naceae family and the genus Solanum. The Solanum genus was found to exhibit anticariogenic activity and was tradition-ally used to treat oral diseases. However there are no scien-tific studies done specifically for Solanum ferox L. Hence the aim of the study is to determine the anticariogenic properties of flesh and leaf of ethanolic extract of Solanum ferox L. Alka-loids, flavonoids and tannins were detected in the leaf etha-nolic extract via preliminary phytochemical screening. The presence of these phytochemicals may contribute to the anticariogenic activity. Treatment with different concentra-tions of flesh and leaf of ethanolic extract were used against Streptococcus pyogenes and Staphylococcus aureus via the method of agar well diffusion to indicate zones of inhibition. The antibiofilm activity of the flesh and leaf ethanolic extracts was tested. The flesh and leaf ethanolic extracts possess sig-nificant (p<0.05) dose-dependent on antimicrobial activity and positive antibiofilm activity against respective pathogens. Flesh ethanolic extract has stronger anticariogenic activity compared to leaf ethanolic extract against Staphylococcus aureus. Streptococcus pyogenes exhibited higher susceptibil-ity as compared to Staphylococcus aureus. In conclusion, it has been shown that the ethanolic extract of Solanum ferox L. exhibit anticariogenic properties against Streptococus py-ogenes and Staphylococcus aureus